Use of Illegally Distributed Books in Lithuania - Grigas, Vincas; Gudinavičius, Arūnas; Černevičiūtė, Emilija (Information & Media, 2021)
This study seeks to reveal the attitudes of the Lithuanian adult population on using digital books and illegally distributed books and seeks to provide possible solutions to Lithuanian publishers and other institutions combating this phenomenon. A quantitative survey of 322 respondents was conducted. The analysis of the results was based on the Technology Acceptance Model, the theory of self-efficacy and the theory of planned behaviour. The results show that the ability to use digital technologies encourages the use of digital books. The perception of digital books as having value reduces the tendency to download them from illegal distribution channels. Legislative regulation does not have a significant impact on the intention not to use digital books from illegal distribution channels. It is likely that a negative assessment of the phenomenon in the immediate environment will have a greater impact on refusing to use illegally distributed books. In order to compete with illegal distribution channels, the channels for legally distributed books need to be more convenient and provide more content.